RADIO KOMUNITAS SEBAGAI TEKNOLOGI TEPAT GUNA UNTUK KOMUNIKASI MASYARAKAT - Rustamaji, Rustamaji; Sawitri, Kania (Universitas Borneo Tarakan, 2023)
At this time there are various types of equipment for electronic communication or often called telecommunications equipment that can be used by the public. Difficulties for students who do not have or master the use of the latest telecommunications equipment, and live in areas that are not covered by telecommunications networks. Of course there must be an appropriate alternative technology that can be used. Where one of them uses broadcast technology through